2002
DOI: 10.3748/wjg.v8.i6.1134
|View full text |Cite
|
Sign up to set email alerts
|

Effects of recombinant human growth hormone on rat septic shock with intraabdominal infection byE. coli

Abstract: rhGH showed beneficial effects on rat septic shock. The possible mechanisms may involve the attenuation of bacteria/endotoxin translocation and decreased systemic endotoxin level; inhibition of the production and release of TNFalpha; improved circulatory function; improved systemic host defenses and maintenance of intestinal mucosa barrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 34 publications
0
15
2
1
Order By: Relevance
“…Some studies have indicated that treatment with GH is safe and beneficial for patients with mild sepsis and severe sepsis, as well as for critically ill patients without sepsis. We have previously demonstrated that rhGH can improve the circulatory function and increase the survival of rats in septic shock (5). However, it has been demonstrated that administration of rhGH to long-stay critically ill adults increases morbidity and mortality (18,19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have indicated that treatment with GH is safe and beneficial for patients with mild sepsis and severe sepsis, as well as for critically ill patients without sepsis. We have previously demonstrated that rhGH can improve the circulatory function and increase the survival of rats in septic shock (5). However, it has been demonstrated that administration of rhGH to long-stay critically ill adults increases morbidity and mortality (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Both animal and human studies have demonstrated that recombinant human growth hormone (rhGH) can enhance protein synthesis, promote tissue recovery, stimulate intestinal epithelial growth, etc. (3)(4)(5). However, the mechanism of the protective effect of rhGH on the intestinal mucosa barrier is not understood.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrated that rhGH might protect the damage of the intestinal mucosa by inhibiting apoptosis of intestinal mucosa cells and increasing of IGF-1 levels (11,15,17,25). The biological effects of GH are indirectly mediated by IGF-1.…”
Section: Discussionmentioning
confidence: 99%
“…The biological effects of GH are indirectly mediated by IGF-1. IGF-1 can prevent intestinal atrophy in septic rats and protect the integrity of intestinal structure (11,12,13,18,21). Gary et al reported that the development of bacterial translocation is inversely correlated with serum IGF-1 levels and treatment with IGF-1 decreased enterocyte apoptosis (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation